EL PRINCIPIO DE CONTINUIDAD EN LA PRESTACIÓN DE SERVICIOS PÚBLICOS DE TELECOMUNICACIONES - Gonzáles Prada, Carlos (Revista de Derecho, 2019)
This article develops the main characteristics and scope of the principle of continuity in the provision of public telecommunications services, in order to determine whether said principle should or not be understood literally as the requirement of an uninterrupted service or if, otherwise, its enforcement may admit interruptions under certain parameters of tolerance. For this purpose, first we will review the notes that define the notion of public services, and in particular the obligation to guarantee its provision in a continuous manner. Subsequently, we will analyze how the aforementioned principle materializes in the telecommunications sector. Lastly, we will evaluate the content of article 44 of the Consolidated Text of the Conditions of Use of Public Telecommunications Services, in order to obtain a valid and reasonable interpretation for the sector.